Effects of Vitamins C and E on Oxidative Stress among Diabetes Mellitus Type 2 Patients in Gaza City, Palestine - Eman Seyam; Marwan O. Jalambo; Mohammed Shubair (Proceedings)
Oxidative stress is defined as the excessive production of reactive oxygen species (ROS) and reactive nitrogen species in the presence of diminished antioxidant substances. It has been shown that oxidative stress disrupts the normal glucose metabolism in type 2 diabetic patients. The authors aimed to study the effect of vitamins C and E on oxidative stress among diabetes mellitus Type 2 patients in Gaza City, Palestine. The purpose of this study was to evaluate the effects of vitamins C and vitamin E as an adjunctive therapy in reducing the Erythrocyte Sedimentation Rate, Malondialdehyde (MDA), hs-CRP, and Total cholesterol in the sera of type 2 diabetes mellitus patients in Gaza City. To achieve this study, one hundred and sixty-eight (168) diabetic patients were selected from Gaza City. The diabetic patients (117) were treated with anti-diabetic agents such as metformin and divided into three groups; the first group was a control group that received anti-diabetic agents metformin only; the second group received vitamin C (1000 mg) along with metformin; whereas the third group received vitamin C (1000 mg) and vitamin E (400 mg), together along with metformin. All patients were followed up for 3 months. The results showed more significant reductions in the MDA, Hs-CRP, and cholesterol levels among the patients who used vitamin C and combinations of vitamins C and E compared to those of the control group after 3 months. The reduction of MDA is larger in the vitamin C and E group than it was in the vitamin C group alone, and the reduction in cholesterol was similar in both groups, but there was not any improvement in the level of ESR. The study revealed that the use of antioxidants like vitamin C and vitamin E can decrease the severity of oxidative stress and decrease the level of inflammatory markers, and it improves the total cholesterol level, so antioxidants can improve diabetes mellitus and its complications.